PENGARUH PENGGUNAAN MODEL ON BOARD PICTURE STORIES TERHADAP HASIL BELAJAR SEJARAH SISWA KELAS XI IPA DI SMA N 5 PADANG - Suryadinata, Fandi - (Pendidikan Sejarah, 2014)
This research is motivated by the inefficiency in the use of learning methods in thelearning process, there are students who pay less attention to the material presented by the teacherand many students are in and out during the learning process takes place. On the basis of theproblem of this study focused on the effect of applying the Model On Board Picture Stories OfHistory Student Learning Outcomes in class XI Science SMAN 5 PADANG. The research is aquantitative study, in which data is obtained through direct experimentation in class XI ScienceSMAN 5 Padang. The selection of the sample is taken by simple random sampling, in order toobtain the experimental class is class 1 and class XI Science control is a class XI Science 2. Theresults of this study indicate that the learning outcomes of the historical average over Tinggihexperiment class of control class. This is evident from the difference value of 85.62 posttestexperimental class and control class posttest value of 78.45 with a hypothesis test is 2.66 whilet_tabel t_hitung 2.00 from the analysis of the results of research and discussion, it can beconcluded that the application of the Model On Board Picture Stories significant effect on learningoutcomes history class XI science in SMA N 5 Padang. For it is concluded that the teachers canuse Model Picture Stories On Board to increase the liveliness and creativity of students.